2019
DOI: 10.1002/cyto.a.23919
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Phenotypic Profiling of 27 DLBCL Cases Reveals Marked Intertumoral and Intratumoral Heterogeneity

Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common histologic subtype of non‐Hodgkin lymphoma and is notorious for its clinical heterogeneity. Patient outcomes can be predicted by cell‐of‐origin (COO) classification, demonstrating that the underlying transcriptional signature of malignant B‐cells informs biological behavior in the context of standard combination chemotherapy regimens. In the current study, we used mass cytometry (CyTOF) to examine tumor phenotypes at the protein level with single cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…To our knowledge, this is the first immune profiling of the myeloid compartment in lymphoma tumors by mass cytometry. Prior work has characterized T cells and B cells in FL, DLBCL, and HL using mass cytometry [38,40,41] and characterized myeloid cells in lung and breast cancer [11,13]. The resolution of the complex, heterogeneous lymphoma microenvironment by mass cytometry was striking when compared to prior low-dimensional studies measuring fewer than eight markers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first immune profiling of the myeloid compartment in lymphoma tumors by mass cytometry. Prior work has characterized T cells and B cells in FL, DLBCL, and HL using mass cytometry [38,40,41] and characterized myeloid cells in lung and breast cancer [11,13]. The resolution of the complex, heterogeneous lymphoma microenvironment by mass cytometry was striking when compared to prior low-dimensional studies measuring fewer than eight markers.…”
Section: Discussionmentioning
confidence: 99%
“…To further support the notion that C5/MCD reflects a MB COO, we conducted CyTOF on patients from an independent DLBCL cohort (Table S6) (Nissen et al, 2019). Cells from reactive LN specimens were used to define B cell subpopulations.…”
Section: Human Mcd/c5 Tumors Show Evidence Of Mb Originmentioning
confidence: 99%
“…Clinic-pathological characteristics of these cases are detailed in the original publication. For CyTOF immunoprofiling, diagnostic pre-treatment LN biopsies from patients with DLBCL, or non-malignant ''reactive'' LN (rLN) were acquired from the lymphoma tumor bank at the BC Cancer Agency (as described in Nissen et al, 2019), and were selected based on sufficient numbers of viable cells for CyTOF analysis (2 million per sample). Clinic-pathological characteristics of these cases are detailed in the original publication.…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very special barcoding technique using palladium isotopes has been applied in the paper by GK Behbehani (Behbehani et al, ), where an extensive study of myelodysplastic syndromes (MDS) by 34‐parameter mass cytometry is illustrated. Mass cytometry is a mature analytical technique that can be applied today outside its traditional research boundaries, as shown in many recent valuable papers on leukemia, myelodysplasia (Zeng et al, ; Das Gupta et al, ; Nissen et al, ; Wierz et al, ; Bandyopadhyay et al, ), immunological studies (Leipold et al, ) and even erythroid development (Thomson‐Luque et al, ). Mass cytometry allows for the analysis of cell heterogeneity on a very large scale, theoretically measuring up to 100 different cell features simultaneously with metal isotope‐tagged antibodies without any spectral overlap (Olsen et al, ).…”
mentioning
confidence: 99%